WEB-BASED BEKONANG VILLAGE DESTINATION RECOGNITION MANAGEMENT - Lestari, Dewi Amelia; Purwandari, Suci (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The tourism sector is one of the potential sectors to be developed in modern times today, but not all tourist spots can thrive. One of the factors that led to the lack of development of tourist attractions is the lack of promotion or delivery of information to tourists. The development of the internet is now more advanced so much utilized by the manager of tourist attractions as a medium of information and promotion. Bekonang tourist village in Mojolaban area has the potential to be more developed. For that reason the need to utilize the internet by designing the village website Bekonang tourism as a medium of information and promotion. Research conducted to design the website using waterfall method and using data collection techniques in the form of interviews, observation, and literature study. While the software used in designing Bekonang village tourist website is XAMPP, Dreamweaver and using programming languages such as HTML, PHP, CSS, Java Script, and JQuery. The result of this observation and research is that the researcher succeeds in creating Bekonang Village Tourism website which can be used as information and promotion to improve and facilitate the tourists who want to visit Bekonang Tourism Village